Penggunaan Metode Jarimatika untuk Berhitung Cepat dan Tepat Bagi Siswa Kelas V di Sekolah Dasar Negeri Bagu - Fadli, Saiful; Solihah, Fatimatus; Akbar, Lalu Ajimuliardi; Rahmawati, Helmi; Diana, Diana (Takuana: Jurnal Pendidikan, Sains, dan Humaniora, 2026)
Mathematics is basically dominated by arithmetic operations, both addition, subtraction, multiplication and division, so if students want to master mathematics then students must be able to count correctly. One method that can be applied to train students' counting skills is by using the jarimatika method. This PKM activity aims to train fast and accurate counting skills in mathematics learning for grade V SDN Bagu. The method used in the PKM activity is the lecture and demonstration method. In addition to seeing the results of this PKM, an evaluation was carried out by looking at the responses of students after this PKM activity was carried out. The results of the PKM activity were the responses of most students or more than more than 80% of students gave a very good response to this PKM activity, students felt that counting using Jarimatika became easy and counting became faster and more accurate.